Comparison of outcomes for cancer patients discussed and not discussed at a multidisciplinary meeting. (August 2017) - Rogers, M.J.; Matheson, L.; Garrard, B.; Maher, B.; Cowdery, S.; Luo, W.; Reed, M.; Riches, S.; Pitson, G.; Ashley, D.M.
Abstract: Objectives: Comparison of outcomes for cancer patients discussed and not discussed at a multidisciplinary meeting (MDM). Study design: Retrospective analysis of the association of MDM discussion with survival. Methods: All newly diagnosed cancer patients from 2009 to 2012, presenting to a large regional cancer service in South West Victoria, Australia (620 colorectal, 657 breast, 593 lung and 511 haematological) were recorded and followed up to 5 years after diagnosis. Treatment patterns and survival of patients whose treatment was discussed at an MDM compared to those who were not, were explored. Results: The proportion of patients presented to an MDM within 60 days after diagnosis was 56% ( n = 366) for breast cancer, 59% ( n = 363) for colorectal cancer, 27% ( n = 137) for haematological malignancies and 60% ( n = 355) for lung cancer. Seventy-three percent ( n = 886) of patients discussed at an MDM had their tumour stage recorded in their medical records while only 52% ( n = 604) of patients not discussed had their tumour stage recorded ( P < 0.01). We found for haematological and lung cancer patients that those presented to an MDM prior to treatment had a significant reduction in mortality (lung cancer hazard ratio [HR] 0.62, 95% confidence interval [CI] 0.50–0.76, P < 0.01) (haematological cancer HR 0.58, 95% CI 0.35–0.96, P = 0.03) compared to patients whose cases were not discussed at an MDM after adjusting for the potential cofounders of age, stage, comorbidities and treatment. This was not the case for colorectal and breast cancer patients where there was no significant difference. Conclusion: MDM discussion has been recommended as best practice in the management of cancer patients, however, from a public health perspective this creates potential issues around access and resources. It is likely that MDM presentation patterns and outcomes across tumour streams are linked in complex ways. We believe that our data would demonstrate that these patterns differ across tumour streams and that more detailed work is required to better allocate relatively scarce and potentially costly MDM resources to tumour streams and patient groups that may get the most benefit. Highlights: The association between multidisciplinary meetings (MDM) in cancer care and survival is tumour-stream or risk-profile specific compared to patients not discussed at an MDM. Haematological and lung cancer patients whose care plan is discussed at an MDM prior to treatment have a significant reduction in mortality. In contrast, such a benefit could not be demonstrated for colorectal and breast cancer patients.